Does positive feedback support the stronger and weaken the weaker? The effects of supervisors’ positive feedback on newcomers’ task performance in the first 90 days - Atnafu A. Wondim (AOSIS, 2021)
Purpose: This study aims to provide empirical evidence of how supervisors’ positive feedback plays a crucial role in newcomers’ task performance in the first 90 days of their employment.